Engineered nanomaterials and the microbiome: assessing disruptions in environmental and human microbial communities - Chowdhury, Alonkrita; Ghosh, Mayukh (Frontiers in Nanotechnology, 2025)
The rapid advancement and integration of engineered nanomaterials (ENMs) into consumer products, industrial processes, biomedical applications, and environmental technologies have revolutionized multiple sectors. However, their increased production and environmental release raise critical concerns about unintended interactions with microbial ecosystems. ENMs, including metal-based nanoparticles (silver, titanium dioxide, zinc oxide) and carbon nanomaterials (graphene, carbon nanotubes), possess unique physicochemical properties such as high surface area-to-volume ratios, tunable reactivity, and antimicrobial potential that allow them to interact directly with microbial cells or indirectly influence their habitats. This review critically examines the emerging evidence on ENM–microbiome interactions across human, aquatic, terrestrial, and agricultural systems. In human-associated microbiomes, especially the gut, ENMs can induce dysbiosis by disrupting microbial diversity, altering metabolite production (e.g., short-chain fatty acids), and impairing gut barrier integrity, contributing to inflammation and metabolic disorders. In environmental settings, ENMs influence key microbial functions like nitrogen fixation, organic matter decomposition, and biogeochemical cycling, potentially undermining ecosystem stability and agricultural productivity. Moreover, ENMs are increasingly implicated in accelerating antimicrobial resistance by promoting horizontal gene transfer and enriching resistance genes in microbial communities. The review highlights methodological advances such as high-throughput sequencing, meta-omics approaches, in vitro colon simulators, and in vivo models that have enhanced the assessment of ENM-induced microbiome alterations. Despite these advances, significant gaps remain in understanding long-term and low-dose effects, dose–response relationships, and ecological thresholds. Addressing these gaps through multidisciplinary research and regulatory frameworks is essential for ensuring the safe and sustainable deployment of nanotechnologies in a microbiome-sensitive world.